Attitude Calculation Based on Sequential Correction of Gravity Field and Geomagnetic Field (Xibei Gongye Daxue Xuebao, 2020)
Aiming at the problems of gyroscope error divergence and magnetometer susceptibility to soft magnetic environment in attitude calculation of unmanned system, a method of attitude calculation based on gravity field and geomagnetic field sequential correction is proposed. In this method, gyroscope output is used to construct the state equation of attitude quaternion, and then the quaternion is sequentially corrected twice by using accelerometer and magnetometer data in order to obtain accurate attitude output. The experimental results show that, compared with the three traditional attitude calculation algorithms, this algorithm can effectively suppress the gyroscope drift error and improve the attitude output accuracy under the environment of magnetic interference. The static accuracy of the attitude angle is not greater than that of the dynamic accuracy, which meets the application requirements of the unmanned system.